2022
DOI: 10.3389/fphar.2021.791841
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Alleviates Endothelial Glycocalyx Degradation and Promotes Glycocalyx Restoration via TLR4/NF-κB/HPSE1 Signaling Pathway During Inflammation

Abstract: Tetramethylpyrazine (TMP), a Chinese traditional herbal extraction widely used in treating cardiovascular diseases, could attenuate vascular endothelial injuries, but the underlying mechanism remains incomprehensive. Vascular glycocalyx coating on the endothelium would be damaged and caused endothelial dysfunction in the inflammatory microenvironment, which was the initial factor of morbidity of many vascular diseases, such as atherosclerosis (AS). Here, we thoroughly investigated the molecular mechanism of TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In the present study, TMP-PF alleviated atherosclerosis progress by reducing hyperlipemia and inhibiting plaque angiogenesis, which partially clarified the anti-atherosclerotic effects of the Rhizoma Chuanxiong-Radix Paeoniae Rubra herb pair. Previous studies showed that TMP had anti-inflammatory, anti-apoptotic, anti-oxidative, anti-platelet and endothelial cells protection effects in the treatment of cardio-cerebrovascular diseases, such as atherosclerosis, myocardial ischemia and hypertension [26], it was capable of regulating lipid levels and attenuating oxidative stress, inflammatory responses and endoplasmic reticulum stress in gestational diabetes mellitus model mice [27]; TMP suppressed endothelial glycocalyx degradation and protected integrity of glycocalyx structure during inflammation, which might be considered a novel strategy in the treatment of atherosclerosis [28]. Previous studies also showed that PF had anti-hyperglycaemic, anti-inflammatory, anti-oxidative and anti-apoptotic effects, and it attenuated ox-LDL-induced injury in endothelial cells by inhibiting apoptosis and activating autophagy [29],…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, TMP-PF alleviated atherosclerosis progress by reducing hyperlipemia and inhibiting plaque angiogenesis, which partially clarified the anti-atherosclerotic effects of the Rhizoma Chuanxiong-Radix Paeoniae Rubra herb pair. Previous studies showed that TMP had anti-inflammatory, anti-apoptotic, anti-oxidative, anti-platelet and endothelial cells protection effects in the treatment of cardio-cerebrovascular diseases, such as atherosclerosis, myocardial ischemia and hypertension [26], it was capable of regulating lipid levels and attenuating oxidative stress, inflammatory responses and endoplasmic reticulum stress in gestational diabetes mellitus model mice [27]; TMP suppressed endothelial glycocalyx degradation and protected integrity of glycocalyx structure during inflammation, which might be considered a novel strategy in the treatment of atherosclerosis [28]. Previous studies also showed that PF had anti-hyperglycaemic, anti-inflammatory, anti-oxidative and anti-apoptotic effects, and it attenuated ox-LDL-induced injury in endothelial cells by inhibiting apoptosis and activating autophagy [29],…”
Section: Discussionmentioning
confidence: 99%
“…However, upstream of HPSE upregulation and release, only a few specific signalling pathways have been identified, all of which are pathophysiologically relevant in sepsis. These include the angiopoietin-1/Tie2 ligand receptor system, tumor necrosis factor (TNF)-alpha/ TNF receptor signalling and toll-like receptor (TLR)-2 and − 4 signalling [2,3,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%